Respon Uni Eropa terhadap Ancaman Human Security atas Kasus Kematian Mahsa Amini di Iran - Razita, Sarah (Peneliti.net, 2025)
Human security is an issue that has recently become a hot topic of discussion among international relations scientists. This issue resurfaced after the incident that killed Mahsa Amini, an Iranian civilian who died because of the violence of the state apparatus in Iran. This event has also attracted the attention of many parties, including the European Union. The European Union views the actions taken by the Iranian authorities as very arrogant. The European Union also condemned Iran.